The Comparative Analysis of the Internet Banking Among Thai Commercial Banks - San Yee, Nan San (Journal of Buddhist Psychology, 2020)
This study is the result of qualitative research using comparative and analytical methods. The comparative research was conducted by investigating the availability of basic services and the comparison different features offered by banking institutions among five Thailand banks. For that purpose, reviews of website from selected banks are conducted. Besides analyzing the availability of the Internet banking basic services and the differences of the features, the paper will also delineate problems that facing the institution among Thai Bank. The study intends to compare differences and similarities systems of internet banking offered and compare the availability of internet banking features between five Thai banks. The primary source of the information in this research study is individual interview of internet banking officer by using accidently sampling; they offer comprehensive internet banking as known as core banks in order to get their Internet banking services and secondly resources using a combination of knowledge of Websites and search tools to discover and all the available Journals, Articles, papers provided necessary information to finalize the research study. The result of the comparative study indicates that all five Thai banks are dissimilar in providing basic services offered by their commercial banks, among five Thai banks are currently offering the same standard of services. In comparison, only two banks Siam Commercial Bank and Bank of Ayudhya are identified to be offering the same service is fixed deposit placements. Finally, Kasikorn Bank, Bank of Ayudhya and Krung Thai Bank were among the banks listed not offering service as requesting for the bank statements. Specially, only Siam Commercial Bank enhance the best banking via the internet and likely to interesting as the internet banking winner offering all services listed by the researcher. Overall, the researcher found all banks are less sophisticated and will need to improve in offering internet banking for their customers. For recommendation, investments are required by the banks operator in upgrading and improving the quality of their service, not just only on number of services or features offered, but also the quality wise of processing time and reliability or accessibility for customer convenience